The Lifeguard : Poems 2008-2013. - Wedde, Ian (Auckland University Press, 2013)
Ian Wedde's latest collection of poems are a complex mix of rhapsody, fear, and humor, and the prose explore the contradictions between life's pool-side surfaces and frightening undertows. Opening with a major new series of poems "The Lifeguard," it concludes with another long sequence, "Shadow Stands Up," in which a world of Platonic memory and tidal recurrence is observed from a window-seat in Auckland's conspicuously green-branded Link bus. Bringing together work from the past five years by one of New Zealand's most outstanding contemporary page.